Gas temperature in transient CO2 plasma measured by Raman scattering. (20th March 2015) - Brehmer, F; Welzel, S; Klarenaar, B L M; van der Meiden, H J; van de Sanden, M C M; Engeln, R
Abstract: Rotational Raman scattering on the vibrational ground state of CO2 was performed to determine the gas temperature in narrow-gap dielectric barrier discharges (DBDs). The Raman spectrometer was equipped with a straightforward spectral filtering to mask ca. 30 cm −1 (0.85 nm) centered around the excitation wavelength of 532 nm. Linearisation of the observed transitions ( J  = 18–42) was applied to retrieve gas temperatures in discharge gaps of 1 mm. The DBD was operated in pure CO2 at atmospheric pressure and non-negligible gas heating of about 160 K was observed at 33 W injected power. Based on a simplified energy balance the gas temperature measurements were extrapolated to a broad range of injected plasma power values (0–60 W).